Safety of Propofol in Patients Undergoing Endoscopy and Colonoscopy (Medical Forum Monthly, 2025)
Objective: To evaluate the safety profile of propofol sedation in patients undergoing endoscopy and colonoscopy.Study Design: A retrospective observational studyPlace and Duration of Study: This study was conducted at the department of Medicine and Gastroenterology, PAF Hospital, Islamabad, from January 2019 and September 2024.Methods: Inclusion criteria encompassed all adult patients (≥18 years) who received propofol for sedation during endoscopy or colonoscopy. Patients with incomplete medical records, those who received sedation other than propofol, or those with contraindications to sedation were excluded. Data collection included demographic information, comorbidities, procedure details, sedation-related parameters, safety parameters evalauation, and procedural outcomes.Results: In a total of 6220 patients, 4806 (77.3%) underwent upper endoscopy whereas 1414 (22.7%) had colonoscopy performed. There were 3492 (56.1%) male patients. The mean age was 53.28±15.70 years. The mean propofol induction dose was 0.6±0.1 mg/kg in patients undergoing upper endoscopy, and 0.7±0.2 mg/kg in those undergoing colonoscopy (p<0.001). The mean procedure duration in patients undergoing upper endoscopy, and colonoscopy were 18.25±4.77 minutes, and 21.59±5.24 minutes (p<0.001), respectively. Procedural complications were reported in 108 (1.7%) patients, and the most common complications were respiratory depression, and hypotension, noted in 37 (0.6%), and 30 (0.5%), patients, respectively. Procedural success was reported in 6189 (99.5%) patients. The mean recovery time was significantly higher in patients undergoing colonoscopy (32.1±6.1 minutes vs. 30.5±5.2 minutes, p<0.001).Conclusion: This study reaffirms the safety and efficacy of propofol sedation in gastrointestinal endoscopy. With high procedural success rates, minimal adverse events, and rapid recovery times, propofol remains the sedative of choice for endoscopic procedures.